2022
DOI: 10.1093/hropen/hoac024
|View full text |Cite
|
Sign up to set email alerts
|

Plasma level of mannose-binding lectin is associated with the risk of recurrent pregnancy loss but not pregnancy outcome after the diagnosis

Abstract: STUDY QUESTION Are low or high plasma mannose binding lectin (p-MBL) levels associated with recurrent pregnancy loss (RPL) and the reproductive and perinatal outcomes before and after RPL? SUMMARY ANSWER The prevalence of low p-MBL levels was significantly higher in RPL patients while high levels were significantly less prevalent. No association was found between p-MBL level and reproductive and perinatal outcomes before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…We have in repeated studies in different populations of RPL patients and controls found that low levels of p-MBL are associated with increased risk of RPL with ORs between 1.46 and 1.79 ( 23 , 24 ). Moreover, the most recent study high p-MBL levels (≥3000µg/l) seemed to protect against RPL ( 23 ). In the present study, most blood samples were taken prior to pregnancy whereas 10.2% were taken in the first trimester.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have in repeated studies in different populations of RPL patients and controls found that low levels of p-MBL are associated with increased risk of RPL with ORs between 1.46 and 1.79 ( 23 , 24 ). Moreover, the most recent study high p-MBL levels (≥3000µg/l) seemed to protect against RPL ( 23 ). In the present study, most blood samples were taken prior to pregnancy whereas 10.2% were taken in the first trimester.…”
Section: Discussionmentioning
confidence: 95%
“…The p-MBL level was determined with the enzyme-linked immunosorbent assay (ELISA) method as described by Nørgaard-Pedersen et al. ( 23 ). A low p-MBL level was defined as ≤500 µg/l, which is the cut-off value used routinely in Danish laboratories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MBL concentration is largely inherited from parents, and its concentration is typically low in normal plasma [ 81 ]. The liver plays a crucial role in increasing MBL production during the acute-phase reaction of the innate immune response [ 20 ].…”
Section: Complement Component Mannose-binding Lectinmentioning
confidence: 99%
“…Early childhood infections are more common in those with MBL deficiencies, highlighting the importance of the MBL pathway for host defence [ 80 ]. The age range during which infections linked to MBL deficiency may occur demonstrates the significance of innate host defence mechanisms during childhood, before the child’s adaptive immune response reaches its full potential [ 81 ].…”
Section: Complement Component Mannose-binding Lectinmentioning
confidence: 99%